Afterword. Topical problems of religious science - Kolodnyj, Anatolij Mykolajovyč (Ukrai͏̈ns'ke relihijeznavstvo, 2006)
Religious Studies is relatively young and at the same time one of the oldest branches of humanitarian knowledge. Ancient because knowledge of religion we find in the works of authors of countries of the ancient world. Young because its components as a science began to be constituted in the system of knowledge only in the eighteenth-nineteenth centuries. To define yourself in your subject of religious studies was much more difficult than other humanities. The complexity of this definition is due primarily to epistemological factors. The point is that you cannot describe the phenomenon of religion with the help of familiar concepts and categories. The peculiarity of religion is that it does not reflect any external to man natural and social forces, but his personal state, which can be called a state of self-determination in the world, the acquisition of the human self.